Mobile educational games user experience elements: a systematic literature review - Syed Yasin, Sharifah Nurulhikmah (2022)
User experience (UX) is a sub-discipline of Human Computer Interaction (HCI) that has received lots of attention from the researchers. UX is a study that focus on the interaction between the users and the end-products. UX extend beyond usability by measuring the user emotional value in using certain products. In recent, years the topic of educational games utilizing mobile game has been thoroughly discussed among the education and computer science researcher especially on usability, acceptance, and user experience. However, many of the studies only covers on usability and acceptance evaluation and still lacking on UX evaluation, particularly for mobile educational games. UX evaluation covers both usability and experience during the system use and this can ensure a more comprehensive mobile educational games evaluation model. Therefore, it is important to identify the appropriate variables in evaluating the UX of the mobile educational games (MEG). This study explores and identify the suitable UX elements for evaluation of MEG. By definition, MEG is a pedagogical or instructional exercise that blends serious intent with joyful elements on mobile platform. A comprehensive UX framework of MEG will assist the MEG designer and developer to evaluate the games to assure the games are effective and engaging in students' learning.